PENGARUH MANAJEMEN LABA TERHADAP PENGHINDARAN PAJAK YANG DIMODERASI OLEH PERTUMBUHAN PENJUALAN - Nia Febriyanti; Faisal Faisal (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of tax avoidance on the earnings management which moderated by sales growth. The independent variable in this study is earnings management. The dependent variable in this study is tax avoidance and the moderating variable is sales growth. Control variables in this study are firm size, leverage, return on asset, growth potential, asset tangibility, liquidity, and age. The population in this study was listed manufacturing company in Indonesia Stock Exchange (IDX) within the year of 2017-2020. The purposive sampling method was used in this study. The total sample was used in this study 236 observations, which came from 59 companies. The hypothesis was tested by Moderated Regression Analysis. The conclusion from the results show that earnings management has a positive significant effect on tax avoidance. Moreover, sales growth moderated the relationship between earnings management on tax avoidance. In addition, control variables from leverage, growth potential, asset tangibility, liquidity has a positive significant on tax avoidance. Meanwhile, firm size and profitability has a negative significant on tax avoidance.